1,55 mkm fiber laser with electronic controlled mode-locking - Hnatenko, O. S.; Neofitnyy, M. V.; Machekhin, Yu. P.; Zarytskyi, V. I.; Zhdanova, Yu. V. (CAOL, 2019)
A projection of an erbium-doped active-fiber laser is offered in this research paper. Mode synchronization method - the nonlinear evolution of mode polarization, is used to ensure the duration of femtosecond pulses. The basis of this method uses liquid crystal controllers polarization, which is controlled by an electrical signal. The proposed scheme and method for obtaining ultrashort pulses are free from the unstable operation of the laser.
Keywords: fiber laser; mode locking; polarizer; liquid crystal cell